2022
DOI: 10.1177/21582440221094593
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Knowledge Management Practices in an EFL Context in Pakistan

Abstract: Currently, English as a foreign language (EFL) teachers are supposed to recognize that, creativity among students can be developed through knowledge management practices. The current study aimed to investigate EFL teachers’ knowledge management practices from learner insight. The explanatory mixed method research design was used to investigate the phenomenon. Quantitative data was collected from 298 A-Level students through a survey questionnaire, and qualitative data was collected through 7 A-Level students t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The Maldives, too, have put great effort into establishing SBPD, where PD coordinators are trained in schools with numerous leadership roles in planning, conducting PD and guiding teachers (Rizwan, 2019). In a recent study in the Maldives, 99.6% agreed that SBPD were conducted in the schools at least three times yearly (Ahmed et al, 2022). However, the principles of the SBPD framework require an ICT-related component and thus leave a gap for online PLC practices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Maldives, too, have put great effort into establishing SBPD, where PD coordinators are trained in schools with numerous leadership roles in planning, conducting PD and guiding teachers (Rizwan, 2019). In a recent study in the Maldives, 99.6% agreed that SBPD were conducted in the schools at least three times yearly (Ahmed et al, 2022). However, the principles of the SBPD framework require an ICT-related component and thus leave a gap for online PLC practices.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, the Maldives still need to formally shift SBPD into virtual networks, although several online learning platforms, like Google Classroom, Google Meet and subject forums, have been conducted, especially during the pandemic (Ministry of Education, 2021). Furthermore, the education analysis report of 2021 showed that after 37 years, the digitalization process is still in the emerging-applying phase on Morel's matrix for ICT integration in schools (Azlifa and Saeed, 2021;Adam, 2015;Adam et al, 2022;Di Biase and Maniku, 2021) with less preparedness for teachers, ineffective in-service training mechanisms, inadequate technological infrastructure, ineffective implementation strategies, unreliable technical support and lack of a holistic ICT policy, remaining as substantial practical gaps in this aspect (Waseela, 2022;Azlifa and Saeed, 2021;Ahmed et al, 2022;Ministry of Education, 2021).…”
Section: Introductionmentioning
confidence: 99%